The Effect of Communicative Language Teaching Method (CLT) on Improving the Understanding and Use of Isim Isyarah for Grade VII Students of MTs Negeri 1 Gorontalo City - Wiranto Talibo; Mukhtar I. Miolo; Damhuri Damhuri (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2025)
This study investigates the effect of implementing the Communicative Language Teaching (CLT) method on students’ understanding of ism isyarah (demonstrative nouns) among seventh-grade learners at MTs Negeri 1 Kota Gorontalo. Employing a quasi-experimental pretest–posttest control group design, the research involved two classes of 30 students each: class VII-9 as the experimental group taught using CLT and class VII-12 as the control group taught through a conventional method. Data were collected through a validated and reliable comprehension test (α = 0.87). Results of the t-test showed a significant difference between the experimental group (M = 74.13) and the control group (M = 68.43) with p < 0.001. The effect size (Cohen’s d = 1.47) indicated a strong impact of CLT on students’ comprehension. These findings confirm that CLT enhances Arabic grammar learning through communicative and interactive activities. Broader adoption of CLT in Arabic instruction is recommended.